Analysis of Factors Related to the Incidence of Hypertension in Karawang Regency - Nizar Azmi; Bambang Setiaji; Endang Suryadi (Eduvest - Journal of Universal Studies, 2026)
Hypertension is one of the non-communicable diseases (NCDs), which is a leading cause of mortality and is often referred to as the silent killer. Based on the results of screening for risk factors of priority NCDs in Kabupaten Karawang (Posbindu PTM and Puskesmas), the incidence of hypertension ranks first among five other diseases: diabetes mellitus, asthma, COPD, heart disease, and obesity. Therefore, the purpose of this study—to analyze factors related to the incidence of hypertension in the Kabupaten Karawang area—is outlined in Analysis of Factors Related to the Incidence of Hypertension in Karawang Regency. This research employed quantitative analysis with a cross-sectional approach. From a total population of 14,239 hypertensive patients at the Tirtajaya Health Center, Rengasdengklok Health Center, and Teluk Jambe Health Center, the Slovin formula yielded a sample of 120 hypertensive patients selected via proportional random sampling. Primary data were collected using validated and reliable instruments: the Food Frequency Questionnaire (FFQ) for dietary patterns and the Physical Activity Scale for the Elderly (PASE) questionnaire for physical activity. Data analysis included univariate, bivariate, and multivariate techniques using logistic regression. The most dominant and significant variables (p < 0.05) related to hypertension incidence in the Kabupaten Karawang area were physical activity, meat consumption patterns, and alcohol consumption. This study is expected to provide analytical results that inform program development, particularly for hypertension control, thereby contributing to improved public health and strategic efforts in managing hypertension in Kabupaten Karawang.